Ethiopia launches agro-advisory service platform directly reaching 82,000 smallholder farmers - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
Ethiopian farmers face serious challenge of production uncertainties associated with climate variability. The Ethiopian Institute of Agricultural Research (EIAR) supported by CIAT, CIMMYT and CCAFS in collaboration with the Ethiopian Meteorological Agency and the Ministry of Agriculture developed a digital agro-climate advisory platform to improve farmers’ management of climate-induced risks, facilitate technology adoption and thereby improve their livelihoods. The platform will contribute to the vision of making Ethiopian agriculture climate-smart by closing the gap between climate information and effective action.